Effect of Vocal Anesthesia on Adult Dental Patients during Covid-19 pandemic period - Mudher MB. Alsunbuli; Marwa A. Attyia; Amer Hassan; Hasanain Faisal Ghazi (University Library System, University of Pittsburgh, 2023)
BACKGROUND: Pain is as a major concern with dental patients. The dentist-patient interaction can reveal the presence of anxiety and fear, which may result in rise of pain. This study aimed to assess vocabulary communication as support to dental anesthesia on the adult dental patient. MATERIALS AND METHODS: This is a prospective, randomized clinical study, conducted from February 2020 through March 2021. Two hundred individuals (112 males, 88 females) of the age range (16 to 84 years) were separated into two groups for testing the level of pain during dental local anesthesia, with vocal communication and without vocal communication. RESULTS: While the control group showed no difference between males and females, there was a difference between the sexes in the experimental group with past dental visits, VAS and injection type having less anxiety (p=0.0001) while with education/VAS having (p£0.01) as appear in sex to age (p£0.05). There was no difference when data were compared by age, or type of anesthesia (inferior alveolar nerve block or infiltration technique). CONCLUSION: Dental anxiety can be alleviated by talking to the patients before the procedure, which could reduce the amount of pain.